Anti-Inflamatory Drug for Myocardial Injury in Acute Coronary Syndrome - Ryan Ranitya (Acta Medica Indonesiana, 2025)
Acute coronary syndrome (ACS) as the acute setting of coronary chronic syndrome has been widely known to have high mortality rates. ST segment elevation of myocardial infarction (STEMI) is one category of ACS which occurs when major coronary arteries are fully blocked acutely and diminish coronary flow leading to myocardial injury and necrosis. Epidemiology data showed that global prevalence varied from 3.8% in patients whose age to 9.5%. The national heart survey of Indonesia also revealed the rising trends of STEMI from 0.63% in 2013 to 1.5% in 2018. STEMI is associated with high mortality despite advanced system and management such as primary percutaneous coronary intervention (PCI).